Penegakan Hukum terhadap Pelanggaran Parkir Liar di Kota Surabaya - Leonardo Benito Maspaitella; Arief Rachman Hakim (CV Rewang Rencang, 2024)
Law enforcement plays a crucial role in maintaining order and legal certainty in society. In the context of parking management, regulations are established to prevent illegal parking practices that may cause inconvenience and economic losses. However, despite the existence of regional regulations, violations in parking arrangements remain prevalent. Law enforcement mechanisms involve both non-judicial and judicial approaches, including investigation, prosecution, and court proceedings against offenders. Challenges in this process include low public compliance, limited resources, and difficulties in coordinating among relevant institutions.